2022
DOI: 10.1088/1755-1315/959/1/012061
|View full text |Cite
|
Sign up to set email alerts
|

Chemical components of different parts of Strychnos ligustrina, a medicinal plant from Indonesia

Abstract: Strychnos ligustrina Blume is one of the potential plants for medicine that has been used by the local community in Indonesia for traditional medicine. Some studies showed that S. ligustrina parts had different activities, such as antimalarial, antibacterial, antimicrobial, antioxidant, and anticancer activities. Triterpenoids, phenolics, tannins, alkaloids, and flavonoids were detected in this species. Different plant parts and grow sites may affect the composition of chemical components. Therefore, the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…Based on the results obtained from several researchers, the S. arvensis has various kinds of phytochemical compounds found in all parts of the plant. The content of these phytochemical compounds in plants can be affected by several factors such as the part of the plant used (Rahayu et al, 2022), harvest time (Hasan et al, 2017), extracting solvent, and the amount of concentration used (Fidiyani et al, 2015), extraction method (Utami et al, 2020), and environmental factors where it grows (Utomo et al, 2020). Different harvest times and plant parts can affect the number of phytochemical compounds detected (Hasan et al, 2017).…”
Section: Phytochemical Compoundsmentioning
confidence: 99%
“…Based on the results obtained from several researchers, the S. arvensis has various kinds of phytochemical compounds found in all parts of the plant. The content of these phytochemical compounds in plants can be affected by several factors such as the part of the plant used (Rahayu et al, 2022), harvest time (Hasan et al, 2017), extracting solvent, and the amount of concentration used (Fidiyani et al, 2015), extraction method (Utami et al, 2020), and environmental factors where it grows (Utomo et al, 2020). Different harvest times and plant parts can affect the number of phytochemical compounds detected (Hasan et al, 2017).…”
Section: Phytochemical Compoundsmentioning
confidence: 99%
“…Strychnos ligustrina Blume commonly known as bidara laut in Indonesia is a deciduous tree and belongs to Loganiaceae family (Rahayu et al, 2022;Syafii et al, 2016). The plants taste bitter in all parts of the plant, especially the roots.…”
Section: Introductionmentioning
confidence: 99%
“…The plants taste bitter in all parts of the plant, especially the roots. In Indonesian people, this plant is commonly used as a traditional medicine: its bark for toothache and burns, root for stomach aches, and seeds and wood for antimalarial effect (Setiawan et al, 2014). Virtual screening found that bioactive compounds, like chlorogenic acid, phyllamycin A, strychnine, and brucine N-oxide, were predicted to have antidiabetic agents (Setiawansyah et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations